Empowering the Economy of the Paringan the Development of Local Potential-Based MSMEs: JEL Classification: O17, O18, R11, L26, D13 - Manda Ayu Febrianti; Lunariana Lubis (Newinera Publisher, 2026)
This study aims to analyze the community empowerment process in Paringan Village, Ponorogo Regency, through the development of cassava-based MSMEs using Kartasasmita's (1996) empowering approach. This study uses a qualitative method with a case study approach through in-depth interviews, observations, and documentation of MSME actors, village governments, and supporting communities. The results show that strengthening technical skills, developing economic capacity, accessing supporting resources, and collaboration between actors are the main pillars of community economic empowerment. Training, assistance with production tools, business capital, and marketing facilitation through bazaars encourage improvements in skills, productivity, and business independence among the community. The existence of MSMEs such as Pitulikur and UD Boohbie not only increases residents' income and creates jobs, but also expands the market network to overseas through collaboration with resellers in Hong Kong. However, challenges remain in the form of low digital literacy, limited sustainable assistance, and a lack of transparency in marketing activities. Overall, empowerment based on local potential in Paringan Village has proven effective in strengthening the village economy in an inclusive and sustainable manner.